Validity and reliability of the Arabic sedentary behavior questionnaire among university students aged between 18-30 years old - Mohammad A. Alahmadi; Khalid H. Almasoud; Amani H. Aljahani; Naweed S. Alzaman; Omar M. Al Nozha; Osama M. Alahmadi; Rola A. Jalloun; Eman M. Alfadhli; Jomana M. Alahmadi; Areeg A. Zuair; Naif S. Alzahrani; Ahmed A. Alahmdi; et al. (BMC, 2023)
Abstract Purpose The study aimed to test the validity and reliability of the Arabic version of the sedentary behavior questionnaire (SBQ). Methods A total of 624 university students (273 males; 351 females, mean age = 20.8 years) were recruited from Taibah University, Madinah, Saudi Arabia. For criterion and constructive validity (n = 352), the Arabic SBQ was compared with total sitting time from the International Physical Activity Questionnaire-short form (IPAQ-SF) and the International Physical Activity Questionnaire-long form (IPAQ-LF). For concurrent validity, the English and Arabic SBQ versions were given concurrently to bilingual university students (n = 122) once. For test-retest reliability, the Arabic SBQ was given twice to participants (n = 150) at a one-week interval. Results Sitting time of IPAQ-SF (7th question: sitting time on weekdays) and IPAQ-LF (21st question: sitting time on weekdays and 22nd question: sitting time on weekends) correlated significantly with total sitting time/week of the Arabic SBQ (r = 0.29, p = 0.003; r = 0.14, p = 0.02, respectively). Motorized transportation measured with the IPAQ-LF correlated significantly with time spent driving in a car, bus, or train from the Arabic SBQ on weekdays and weekends (r = 0.53, p < 0.001; r = 0.44 p < 0.001, respectively). The total sitting time of the Arabic SBQ was inversely correlated with BMI (r = -0.18, p = 0.001). The correlations between the Arabic and the English SBQ versions ranged from 0.25-0.96; p < 0.001 on weekdays and 0.50-0.90; p < 0.001 on weekends. Moderate to good reliability was also found between test and retest for all SBQ items and total score during weekdays (0.72 to 0.8), and weekends (0.64 to 0.87), with exception of the 7th item "play musical instrument", ICC = 0.46). Mean difference of test-retest of the Arabic SBQ was not significantly different from zero for the total sitting time of the Arabic SBQ (t = -0.715, P = 0.476). Conclusion The Arabic SBQ had satisfactory levels of reliability, with total sitting time of the Arabic SBQ correlating significantly with sitting times derived from IPAQ-SF, IPAQ-LF, and the English SBQ versions. Hence, the Arabic SBQ can be used as a tool to measure sedentary behavior among adult Arabs aged between 18 to 30 years old in future epidemiologic and clinical practice.